Oil dependence and economic instability - Conraria, Luís Aguiar (2007)
We show that dependence on foreign energy can increase economic instability by raising the likelihood of equilibrium indeterminacy, hence making fluctuations driven by self-fulfilling expectations easier to occur. This is demonstrated in a standard neoclassical growth model. Calibration exercises, based on the estimated share of imported energy in production for several countries, show that the degree of reliance on foreign energy for many countries can easily make an otherwise determinate and stable economy indeterminate and unstable.